Accounting variables as determinants of systematic risk in Malaysian common stocks - Chun, Loo Sin; Ramasamy, Meharani (Springer Science and Business Media LLC, 1989)
The objective of this paper is to examine the relationship between financial accounting variables and systematic securities risk in a small and developing capital market, namely the Kuala Lumpur Stock Exchange. Factor analysis was used to group and identify the financial variables into independent dimensions. The possible bias due to multicollinearity between accounting data was ameliorated by selecting one representative variable from each factor profile of the firm. Evidence has shown that financial ratios/profitability ratio and, to a certain extent, activity ratio are important determinants of the systematic risk of a common stock. Contrary to most of the reported findings in other markets, the results show a negative relationship between leverage ratio and systematic risk, for which we have no explanation.